2019
DOI: 10.1088/1361-6641/ab11a0
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative dose γ-irradiation effects on material properties of AlGaN/GaN hetero-structures and electrical properties of HEMT devices

Abstract: The effects of γ-ray irradiation on AlGaN/GaN epitaxial layers and on high electron mobility transistor (HEMT) devices have been systematically investigated. The layer structure and HEMT device has been irradiated cumulatively with γ-ray dose of the order of 16 kGy. The x-ray diffraction (XRD) analysis of irradiated sample shows a lowering in full width at half maximum (FWHM) values along (102) and (002) planes in comparison to the pristine sample due to partial annealing effect. A decrease in the in-plane bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
9
23
0
Order By: Relevance
“…The introduced defects modified the native defect structure and achieved a uniform distribution. 18 In our previous studies x-ray photoelectron spectroscopy, 22 x-ray diffraction (XRD), and CL imaging 23 results have shown that c-irradiation has partial annealing effects. These effects cause the reduction of dangling bonds at the surface as a result of oxidation and structural-chemical ordering at the interface.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduced defects modified the native defect structure and achieved a uniform distribution. 18 In our previous studies x-ray photoelectron spectroscopy, 22 x-ray diffraction (XRD), and CL imaging 23 results have shown that c-irradiation has partial annealing effects. These effects cause the reduction of dangling bonds at the surface as a result of oxidation and structural-chemical ordering at the interface.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study involving the use of a similar c-ray dose range to that used in this study, we performed photoluminescence and XRD analysis and observed a reduction in the number of optically active defects as well as a simultaneous redistribution and annealing of defects or traps. 23 The increase in I D and marginal decrease in I G were saturated after or at the third irradiation dose (16 kGy). This trend of saturation in the parameters was similar to that observed in the material parameters.…”
Section: Figures 5a and B Display The Transfer (I D -V G ) And Outputmentioning
confidence: 94%
See 1 more Smart Citation
“…In this regard, several attempts have been made to assess the reliability of GaN HEMTs in the presence of ionizing radiations for specific applications in nuclear reactors and space. Several studies have also reported the sensitivity of GaN HEMT devices towards the ionizing X -Rays [26][27][28] and γ -Rays [28][29][30][31][32]. The impact of γ -Rays irradiation on reported HEMT architectures is compiled in Table I [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also reported the sensitivity of GaN HEMT devices towards the ionizing X -Rays [26][27][28] and γ -Rays [28][29][30][31][32]. The impact of γ -Rays irradiation on reported HEMT architectures is compiled in Table I [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%